Sinus Augmentation with Biomimetic Nanostructured Matrix: Tomographic, Radiological, Histological and Histomorphometrical Results after 6 Months in Humans - Scarano, Antonio; Lorusso, Felice; Staiti, Giorgio; Sinjari, Bruna; Tampieri, Anna; Mortellaro, Carmen (Frontiers in Physiology, 2017)
Background: Many bone substitutes have been applied for sinus regeneration procedures, such as autogenous bone, inorganic bovine bone, porous and resorbable hydroxyapatite, tricalcium phosphate, bioactive glass, and blood clots. The aim of the present study was a tomographic, histological and histomorphometrical evaluation in humans, of specimens retrieved from sinuses augmented with MgHA/collagen-based scaffolds, after a healing period of 6 months. Materials & Methods: Eleven healthy patients and a total of 15 sinuses were included in this study. The maxillary sinuses were filled with commercial MgHA/collagen-based scaffolds (RegenOss®) with a porous three-dimensional (3D) structure (Fin-Ceramica Faenza S.p.A., Faenza, Italy). These grafts have a composite design, that replicate the organization of bone structure, obtained by a technique in which a specific hybrid organic–inorganic composite is spontaneously built by a biological mechanism. The CBCT scans were done before the procedure, after the surgical protocol (T1), and 6 months after sinus surgery (T2) for implantology. Bone specimens were stored in 10% formalin solution, embedded in a glycolmethacrylate resin and sectioned by a high-precision diamond disc. Histologic and histomorphometric analysis were carried out to evaluate the graft reabsorption and bone healing. Results: The mean volume after graft elevation, calculated for each of the 15 sinuses, was 2906 mm3 in the immediate postoperative period (5–7 days), ranging from 2148.8 to 3146.4 mm3. In the late postoperative period (6 months) it was 2806.7 mm3, ranging from 2010.9 to 3008.9 mm3. The sinuses were completely healed and no residual MgHA/collagen-based scaffolds were visible. Osteoblasts appeared actively secreting bone matrix and marrow spaces contained moderate numbers of stromal cells and vascular network. Osteoblasts were observed actively secreting osteoid matrix. The tissues present in the samples were composed of 1.9 ± 1.9% of lamellar bone, 36 ± 1% of woven bone and 58 ± 3.8% of marrow spaces.